2019
DOI: 10.1021/acs.macromol.9b02103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Film Formation of Partially Cross-Linked Water-Borne Secondary Dispersions that Show Skin Formation upon Drying

Abstract: In a previous publication [Macromolecules 2019, 52, 5245− 5254], we described the synthesis of surfactant-free latex dispersions of nanoparticles (NPs) based on emulsification of a preformed proprietary BASF polymer (M n GPC = 5000 g/mol, D̵ = 3), in which the −COOH groups were partially neutralized by using ammonia. The NPs in these dispersions were then partially cross-linked with neopentyl glycol diglycidyl ether (NGDE) to increase the molecular weight, followed by reaction with monoglycidyl ether to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In addition, Winnik et al reviewed the fundamental principles of polymer films cross-linking, and reaction mechanisms of the competition between bond formation and polymer diffusion in latex films. The diffusion extent of cross-linked and non-cross-linked polymers in the formed latex films were monitored via fluorescence resonance energy transfer. ,, Water trapped under the skin slowed the onset of subfilm coalescence and diffusion of polymers, which in turn acted as a plasticizer to increase the diffusion rate of polymers . They showed that the non-cross-linked sample had a greater extent of polymer diffusion than the cross-linked samples .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Winnik et al reviewed the fundamental principles of polymer films cross-linking, and reaction mechanisms of the competition between bond formation and polymer diffusion in latex films. The diffusion extent of cross-linked and non-cross-linked polymers in the formed latex films were monitored via fluorescence resonance energy transfer. ,, Water trapped under the skin slowed the onset of subfilm coalescence and diffusion of polymers, which in turn acted as a plasticizer to increase the diffusion rate of polymers . They showed that the non-cross-linked sample had a greater extent of polymer diffusion than the cross-linked samples .…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the origin of t ′ is addressed in Section 1 in the Supporting Information. We define the FRET parameter as …”
Section: Materials Experimental and Procedures Of Analysismentioning
confidence: 77%
“…2 ) and Coalescence-based ( Fig. 3 ) ( Liu et al, 2019 , Ahmed et al, 2020 , Winnik, 1997 , Sanay et al, 2021 ). Nevertheless, despite the division of these mechanisms, it is clear that they are complementary in some cases, but some take precedence over others.…”
Section: Film Formation Mechanisms In Sffssmentioning
confidence: 99%